Typology of Dairy Production Systems Based on Management Strategies in Paraná State, Brazil - R. C. M. Tramontini; F. I. Bánkuti; M. S. S. Pozza; E. M. Massuda; J. C. Damasceno; A. M. Dias; C. C. B. F. Ítavo; L. C. V. Ítavo; G. T. Santos (Faculty of Animal Science, Bogor Agricultural University, 2021)
This study aimed to analyze the typology of dairy production systems in Paraná State using management characteristics related to nutrition, milking, and technical aspects. We applied, in loco, 105 surveys in dairy production systems - DPS, located in Paraná State, Brazil. Variables related to farm structure, farmer social characteristics, and management practices applied in dairy systems, were collected. Exploratory Factor analysis (EFA) was used and resulted in three management factors, i.e., F1 (Nutrition Management), F2 (Technical Management), and F3 (Milking Management). Using factorial scores, cluster analysis was employed to identify homogeneous groups of dairy production systems. The dairy production systems in G2 (N=84 DPS) was characterized by prioritizing nutritional management (F1), which was the opposite result presented by G1 (N=21 DPS). The structural features and social characteristics of G1 and G2 were compared (T-test). The results indicated a great heterogeneity for the structural and productive characteristics of the analyzed dairy systems and socioeconomic characteristics of their managers. Results also indicate that producers with less structure and scale of production (Group 1), need more technical guidance in production system management. For producers with larger structures and scales of production (Group 2), continuous improvement investments are suggested in the three factors analyzed in this work - nutritional, technical, and milking. Such actions may maintain or increase the production and productivity results in these dairy systems. It is concluded that aspects related to nutritional management are the ones that mark the biggest difference between the cases analyzed, followed respectively by factors of technical management and milking management. Typology of dairy systems that adopt greater attention to nutritional management practices is characterized by a greater production structure and greater productivity when compared to a typology of dairy systems that prioritize actions of technical system management and milking management.